DIGITAL CADASTRE AND ITS ROLE IN CROSS-BORDER DATA INTEGRATION: UZBEKISTAN’S PERSPECTIVE (International Conference on Modern Science and Scientific Studies, 2025)
The development of a digital cadastre system in Uzbekistan has become a crucial factor in enhancing land management, property valuation, and spatial data governance. This study explores the role of digital cadastre in facilitating cross-border data integration, enabling seamless exchange of geospatial information with neighboring countries and international institutions.The research highlights Uzbekistan’s efforts in establishing standardized digital land records, integrating legal, technical, and administrative frameworks to support regional cooperation and international investment. The findings indicate that a robust digital cadastre not only improves land administration efficiency, but also strengthens cross-border collaboration, economic planning, and sustainable land use policies.